2017
DOI: 10.4172/2572-5629.1000131
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of D-Chiro Inositol Treatment in Gestational Diabetes

Abstract: Background: Purpose of this study was to evaluate the role of D-chiro-inositol (DCI) in the metabolic control of women affected by gestational diabetes mellitus (GDM) and to examine the impact on pregnancy and fetal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…However, these dosages are not currently allowed for supplementation. Furthermore, no side effects were observed in patients receiving intervention with DCI (27.5 up 500 mg/day) in the clinical studies available …”
Section: Inositol Safetymentioning
confidence: 92%
See 1 more Smart Citation
“…However, these dosages are not currently allowed for supplementation. Furthermore, no side effects were observed in patients receiving intervention with DCI (27.5 up 500 mg/day) in the clinical studies available …”
Section: Inositol Safetymentioning
confidence: 92%
“…To date, three studies reported the effects on metabolic parameters of supplementation with DCI alone during pregnancy. Di Biase et al observed the effects of a supplementation with 1 g of DCI on 137 pregnant women diagnosed with GDM after the 24th week of gestation. Women were randomized to receive either DCI 500 mg twice a day or no supplement.…”
Section: Clincal Effects Of D‐chiro‐inositol Supplementationmentioning
confidence: 99%
“…Recent literature has provided insight into the use of different stereoisomers of inositol or their combination in GDM treatment [2,38], showing an improvement in fetal growth, glycemic control (post-prandial glycemia and insulin doses), and maternal weight gain in women who received DCI 500 mg twice a day vs placebo [38]; remarkably, a significant reduction in HOMA-IR and a lower need for intensified insulin therapy in women exposed to MI and MI plus DCI (2) have also been demonstrated. In a pilot case-control study, Pintaudi et al [3] found lower mean glucose levels and an improvement in glucose variability after MI treatment in women affected by GDM, suggesting that MI supplementation can be a useful strategy for treating GDM.…”
Section: Inositol Supplementation and Gdm Treatmentmentioning
confidence: 99%
“…The effect of MI and DCI was evaluated in the population of pregnant women diagnosed with gestational diabetes in mono-formulations or in combination. It was found that there is a significant beneficial effect on metabolic factors and reduction of IR in pregnant women diagnosed with gestational diabetes, and according to the results of the study, it has been shown that DCI has a more significant effect than MI [29,30]. The choice of medical treatment including inositols depends on undelaying endocrinological and metabolic disorders and treatment goals.…”
Section: Treatment Of Reproductive Disorders With Inositolsmentioning
confidence: 95%